Advances in genomic, transcriptomic, proteomic, and metabolomic approaches to study biotic stress in fruit crops. (4th July 2019) - Li, Tong; Wang, Ya-Hui; Liu, Jie-Xia; Feng, Kai; Xu, Zhi-Sheng; Xiong, Ai-Sheng
Abstract: Biotic stress is one of the key factors that restrict the growth and development of plants. Fruit crops are mostly perennial, so they are more seriously endangered by biotic stress. Plant responses to different types of biotic stresses such as pathogens and insects are controlled by a very complex regulatory and defense system. High-throughput sequencing (next-generation sequencing) has brought powerful research strategies and methods to the research fields of genomics and post-genomics. Functional genomics, transcriptomics, proteomics, metabolomics, and deep-sequencing of small RNAs provides a new path to better understand the complex regulatory and defense systems behind biotic stress in plants. In this review, we summarized recent progresses in research on fruit crops responses to biotic stress using genomics, transcriptomics, proteomics, metabolomics, and deep-sequencing approaches. This paper also summarized the information of SNP marker resources and the transcription factors that are involved in the regulation of biotic stress responses obtained from genome sequencing, and discusses the differential expression of related genes and proteins identified by transcriptome and proteome sequencing. At the same time, the roles of signaling pathways and metabolites involved in plant biotic stress revealed by the metabolome have also been discussed. In addition, the application of small RNA deep sequencing in the study of fruit crop response to biotic stress has also been included in this review. These omics and deep sequencing methods will greatly support the biotic resistance-resistant breeding of fruit crops.